2021
DOI: 10.1038/s41598-021-97168-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an external compared to an internal focus of attention on the excitability of fast and slow(er) motor pathways

Abstract: The neurophysiological mechanisms underlying the behavioural improvements usually associated with an external (EF) compared with an internal focus of attention (IF) remain poorly investigated. Surround inhibition in the primary cortex has been shown to be more pronounced with an EF, indicating a more spatial restriction of the motor command. However, the influence of different foci on the temporal aspect of the motor command, such as the modulation of fast versus slow(er) motor pathways, remains unknown and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Previous studies using TMS reported no significant difference in the corticospinal excitability of the agonist muscle between the EF and IF conditions in finger 16,17,40 and elbow 41 movements. However, the short-interval intracortical inhibition in the M1 of the agonist muscle was greater in the EF condition than in the IF condition, and the levels of surround inhibition in the adjacent muscle were higher when adopting an EF compared to an IF during force control 16,17 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous studies using TMS reported no significant difference in the corticospinal excitability of the agonist muscle between the EF and IF conditions in finger 16,17,40 and elbow 41 movements. However, the short-interval intracortical inhibition in the M1 of the agonist muscle was greater in the EF condition than in the IF condition, and the levels of surround inhibition in the adjacent muscle were higher when adopting an EF compared to an IF during force control 16,17 .…”
Section: Discussionmentioning
confidence: 72%
“…However, the short-interval intracortical inhibition in the M1 of the agonist muscle was greater in the EF condition than in the IF condition, and the levels of surround inhibition in the adjacent muscle were higher when adopting an EF compared to an IF during force control 16,17 . Moreover, adopting an IF strategy showed higher excitability of slow motor pathways, but not fast motor pathways, in comparison with the EF strategy 40 . Recently, an electroencephalogram (EEG) study further revealed that the IF condition increased the EEG coherence (10)(11)(12) of Alpha 2 between T3 (verbal-analytical region) and Fz (motor planning region) compared to that without any instruction regarding attentional focus, suggesting that an IF strategy might lead to higher real-time conscious motor processing and reduce the accuracy of motor performance 42 .…”
Section: Discussionmentioning
confidence: 89%
“…On the contrary, in the case of an internal focus strategy, the motor control system becomes more constrained, with the direct consequence of depressing motor performance due to more controlled and conscious movement [ 57 ]. Moreover, when using an EF, a more economic strategy is possible because it seems to facilitate altered neural activation de facto, resulting in more intracortical inhibition that reduces the upper motoneurons’ activation, accompanied by a reduced slower motor pathway [ 14 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an EF seems to promote more automatic modes of control and therefore results in an enhanced performance (Wulf, 2013). The idea of the constrained action hypothesis was supported by studies showing an improved neuromuscular strategy (Lohse, Sherwood, & Healy, 2011; Vance, Wulf, Tollner, McNevin, & Mercer, 2004; Walchli, Ruffieux, Bourquin, Keller, & Taube, 2016; Wulf, Dufek, et al, 2010) but also a more efficient brain activation (Kuhn, Keller, Egger, & Taube, 2021; Kuhn, Keller, Lauber, & Taube, 2018; Kuhn, Keller, Ruffieux, & Taube, 2017a; Kuhn, Keller, Ruffieux, & Taube, 2017b) with an EF.…”
Section: Introductionmentioning
confidence: 99%